A versatile bottom-up interface self-assembly strategy to hairy nanoparticle-based 2D monolayered composite and functional nanosheets. Issue 69 (8th August 2019) - Mai, Weicong; Zuo, Yuan; Zhang, Xingcai; Leng, Kunyi; Liu, Ruliang; Chen, Luyi; Lin, Xidong; Lin, Yanhuan; Fu, Ruowen; Wu, Dingcai
Abstract : A universal bottom-up interface self-assembly strategy for fabricating hairy nanoparticle-based 2D monolayered composite and functional nanosheets was presented. Abstract : Herein, we present a universal bottom-up interface self-assembly of hairy nanoparticle strategy for 2D monolayered composite and functional nanosheets, including polymeric composite nanosheets and functional porous polymer and carbon nanosheets. By using diverse hairy nanoparticles as building blocks, a series of 2D monolayered polymeric composite nanosheets was prepared, demonstrating the universality of our strategy. Furthermore, the 2D polymeric composites could be easily transformed into 2D monolayered functional porous polymer and carbon nanosheets. We hope that this strategy will open a new door for the design and fabrication of advanced 2D composite and functional nanosheets and thus provide new opportunities for different fields including the environment, energy, catalysis and medicine.